Projeto ético-político da Psicologia da Libertação: perspectiva histórica - Pereira, Thiago Sant'Anna (2013)
The objective of this research is - through historical research to understand the process of construction of the ethical-political project of the Liberation Psychology, in the textual work of Ignacio Martín-Baró. We used the materialism historical-dialectical as the theoretical referential. From our main research we have unfolded the following specific goals: a) understanding the historical roots of Martin-Baró´s thoughts b) identification of the main concepts of this author in the construction of a Liberation Psychology. The intellectual formation of Martín-Baró gave him a theoretical versatility uncommon in the recent history of Latin American´s psychosocial theories. His ethical-political project was directly influenced by horizon (quefazer) named by himself liberation. The concept was born of Latin American Liberation Theology, however his theory gives concrete connotation to it - it is not, just metaphysics liberation, but of the conditions of socio-political and economic oppressions. Beyond the Liberation Theology, Martín-Baró was influenced by existentialism and psychoanalysis (at first), later (more clearly) by the marxist theories. His theoretical project is characterized as revisionist-critical, and its ethics are based on the defense of specific interests of the exploited classes. The main concepts / categories and elements studied were: awareness, group processes, activity-conduct-attitude-action-political behavior, socialization, identity, ideology-ideologization, public opinion, fatalism, power, violence, specifics of war, religion, university and liberation. We also expose the ontological foundations that sustain its theoretical support. For Martín-Baró, the psychology science cannot be asked to intervene in socioeconomic mechanisms that promote inequality, but is encouraged to intervene in the subjective processes of scientific legitimation that support them. This work builds on and integrates researches done by NEHPSI (Núcleo de Estudos de História da Psicologia), which maintain a group of researchers focused on the study of Psychology from Latin America